Psychotropic medications and metabolic side effects in common genetic syndromes with intellectual disability-case report (Kerala Journal of Psychiatry, 2020)
Multi-systemic genetic disorders are strongly associated with psychiatric illness and may require psychotropics for their management. The choice of psychotropics is primarily determined by medical comorbidities and adverse effects.  A careful assessment of behavioural phenotype and metabolic monitoring for children on psychotropics should be followed to avoid adverse consequences.  Hence, the need for monitoring of metabolic syndrome during routine clinical evaluation and the use of aripiprazole which demonstrated a good response with minimal adverse effects are highlighted with a description of cases of children with intellectual disability and neurodevelopmental genetic syndromes like Down Syndrome and Prader-Willi syndrome.
Keywords: Genetic syndromes, Aripiprazole, Down syndrome, Prader-Willi syndrome, cardio-metabolic side-effect